1998
DOI: 10.1002/(sici)1521-4141(199807)28:07<2178::aid-immu2178>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-deficient mice resist myelin oligodendrocyte glycoprotein-induced autoimmune encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is induced by immunization with myelin components including myelin oligodendrocyte glycoprotein (MOG). Myelin-specific Th1 cells enter the central nervous system (CNS) via binding of very late antigen 4 (VLA-4) to the endothelial vascular cell adhesion molecule 1 (VCAM-1). In the present study, mice with a homologous disruption of the gene encoding IL-6 are found to be resistant to MOG-induced EAE as evidenced by absence of clinical symptoms, minimal infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
164
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 289 publications
(171 citation statements)
references
References 35 publications
(37 reference statements)
6
164
1
Order By: Relevance
“…Thus, IFN-γ and TNF-α may be associated with perivascular infiltration, but not with parenchymal infiltration, of inflammatory cells in the CNS in CREAE. IL-6 is a plurifunctional cytokine that is necessary for inducing cerebrovascular adhesion molecules, such as VCAM-1, which are essential for leukocyte trafficking to the CNS during EAE [21]. Other studies on EAE have demonstrated that the formation of CD4 + Th17 cells is driven by IL-6 together with TGF-β [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IFN-γ and TNF-α may be associated with perivascular infiltration, but not with parenchymal infiltration, of inflammatory cells in the CNS in CREAE. IL-6 is a plurifunctional cytokine that is necessary for inducing cerebrovascular adhesion molecules, such as VCAM-1, which are essential for leukocyte trafficking to the CNS during EAE [21]. Other studies on EAE have demonstrated that the formation of CD4 + Th17 cells is driven by IL-6 together with TGF-β [22].…”
Section: Discussionmentioning
confidence: 99%
“…More recently another subset of T-helper cells, Th17, characterized by expression of the transcription factors retinoic acid receptor-related orphan receptor alpha (ROR-α) and retinoic acid receptor-related orphan receptor gamma t (ROR-γt) and by the production of IL-17, has been considered pivotal for the propagation of autoimmune demyelination (3). Mice with impaired numbers or function of Th17 cells, particularly mice deficient in the cytokines IL-6 or IL-23, are largely resistant to EAE (4)(5)(6). However, precise mechanisms governing the development and function of Th17 cells resulting in autoimmune demyelination are still unclear.…”
mentioning
confidence: 99%
“…Its significance in one model system, experimental autoimmune encephalomyelitis (EAE), was supported by a number of studies. One of the most compelling being that IL-6 knockout mice were resistant to EAE (11,15) and had defects in the ability to activate antigen-specific T cells into effector status, despite having apparently normal T cell development (13). The IL-6 promoter contains both canonical KLF4 and CACCC binding sites, which led us to speculate that KLF4 might regulate the transcription of IL-6 and therefore have a downstream effect on production of IL-6.…”
mentioning
confidence: 99%